STUDI PERKEMBANGAN PAKET BIMBINGAN DAN KONSELING ISLAM BAGI GURU MELALUI TEKNIK STORYTELLING UNTUK MENINGKATKAN KETERAMPILAN SOSIAL ANAK USIA DINI (Jurnal Bimbingan dan Konseling Islam, 2013)
This study aims to improve the social skills of early childhood through Storytelling techniques. The end result of this packet calculations on the emotions of children before and after the change of the counseling process, ie before the happy emotions rising 12 points to 19 points, at emotions meingkat smile before the 14 to 19 points, at emotions into neutral before 15 menurn 14 points, the emotional cries before 15 dropped to 10, the sad emotions before 14 dropped to 5, and emotional upset before 15 dropped to 2 and categorized as very effective. Researchers have conducted by practice of Islamic Guidance and Counseling through the storytelling technique has been tested by teachers and the results 80%, then the package that is designed to comply with the standard test is very precise categories.Keywords: Islamic Guidance and Counseling, Social Skill, Storytelling